Kit de brinquedos: uma forma prazerosa de ensinar e aprender física no ensino fundamental I - Sousa, Aldalberto dos Santos (Universidade Federal Rural do Semi-Árido, 2017)
There is a great curiosity of the children for the natural world. They want to know why phenomena happen. What makes an environment conducive to the process of scientific literacy? However, scientific literacy in the initial grades of elementary school is a reality that needs to be better worked out, from the training of teachers to the structure of schools and the materials used in the construction of scientific knowledge. It is also necessary to encourage children to maintain the scientific curiosity that, most of the time, is lost with the passage of time. This work aims to stimulate the interest of students in the Natural Sciences, in particular Physics, through the practice of playful learning activities, using as a pedagogical tool a kit of toys aimed at teaching topics of Physics. The educational product was elaborated from a survey made through the analysis of a textbook of the third grade of Elementary School I, followed by questionnaires with teachers and with the class for which the product was applied. We also sought subsidies in Vygotsky's theory of learning which, in general terms, relates the child's cognitive development to the act of playing. The application of the product was carried out with the third class of Elementary School I. The topics of Physics worked in the classes during the process were: Waves, Light and Colors, Friction, Air Resistance and Balance of Bodies. After each class the teacher applied questionnaires, suggested in the tutorial of the product, on the subjects worked in class. At the end of the process, questionnaires were applied with the teacher and the students of the class, in order to raise the level of satisfaction and learning after using the toy kit. Through the questionnaires applied it was possible to verify that the teacher, using the tutorial, had no difficulty in using the toy kit and that it was well accepted in the class, which shows a good fit of the tutorial of the product. In addition, with the methodology used, it was possible to work the oral language of the children, stimulating them to think, explain the observed phenomena and encouraging them to break the passivity that is usually imposed on them in the traditional approach, enabling the development of autonomy of the students and a better understanding of the studied phenomenon
Keywords: Física no ensino fundamental I; Brinquedos; Alfabetização científica; Physics in elementary school I; Toys; Scientific literacy; CIENCIAS EXATAS E DA TERRA::FISICA